Peninjauan Pelayanan Pindah Lokasi Penimbunan (PLP) di Area Tanjung Priok - Satria Akbar Gumilang; Bungaran Adi Prama; Fakhri Najmuddin (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to find out Minimizing the accumulation of trucking in the operational field, Informing Trucking Drivers if there is a maximum limit for trucks entering PT IPC Terminal Container Tanjung Priok 2 Ocean Going Area. The method used in the preparation of this research is a qualitative method. the data source used is a secondary data source. In obtaining data and information for this research, it was obtained through direct observation or survey during the Receiving and Delivery process at the Gate In Tanjung Priok 2 Ocean Going Area. The results showed that the Tanjung Priok 2 area, especially Ocean Going (International), experienced an increase or surge in trucking flows at the Buffer Area Gate In and service acceleration in the field. In anticipating this, officers are allowed to carry out Gate opening/closing actions.